Justice to-come: Notes on exception, biopolitics and violence in pandemic key - Aulestia Calero, Martín (2022)
This article explores the relationship between the concepts of state of exception, law and violence. According to Carl Schmitt, the sovereign is the one who decides on the state of exception. The exception suspends the law with the purpose of restoring its validity. For his part, Giorgio Agamben has argued that the state of exception has become the paradigm of contemporary government and must be understood as the original structure of modern biopolitics, which ties the living to the legal norm, thus converting it into bare life. Hence the need to ask for a human praxis that escapes the juridical order. Walter Benjamin's concept of divine violence opens possibilities for thinking about a form of violence and praxis that escapes the law and thus makes justice possible, a question that demonstrates its urgency in the context of the COVID-19 pandemic.